2022
DOI: 10.1002/ejoc.202200026
|View full text |Cite
|
Sign up to set email alerts
|

Light as a Tool in Organic Photocatalysis: Multi‐Photon Excitation and Chromoselective Reactions

Abstract: Over the past decades, photoredox catalysis has developed to the big mature field of chemistry. Especially in the field of organic synthesis, more and more sustainable alternatives to conventional synthesis are being developed. Nonetheless, most research activities are focused on the development of new synthetic pathways, utilizing photons as a source of energy for breaking and building of new chemical bonds. We discuss here cases, where selection of the irradiation mode, light intensity (one-, two-photons) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Screening various photocatalysts to identify properties required to initiate the chain reaction revealed that only photocatalysts that are both triplet sensitizers with an E T of ∼60 kcal/mol and highly oxidizing were successful ( Ir-F and 4CzIPN; see the Supporting Information). In order to probe whether a biphotonic pathway could possibly initiate the chain reaction, the initial kinetics were recorded in dependency on the irradiation intensity . It was found that the initial reaction rate increases with the excitation power P (for λ max = 450 nm: product yield ∝ P 0.85 ; for λ max = 415 nm: product yield ∝ P 1.0 ).…”
Section: Resultsmentioning
confidence: 99%
“…Screening various photocatalysts to identify properties required to initiate the chain reaction revealed that only photocatalysts that are both triplet sensitizers with an E T of ∼60 kcal/mol and highly oxidizing were successful ( Ir-F and 4CzIPN; see the Supporting Information). In order to probe whether a biphotonic pathway could possibly initiate the chain reaction, the initial kinetics were recorded in dependency on the irradiation intensity . It was found that the initial reaction rate increases with the excitation power P (for λ max = 450 nm: product yield ∝ P 0.85 ; for λ max = 415 nm: product yield ∝ P 1.0 ).…”
Section: Resultsmentioning
confidence: 99%
“…We note that PBEh-3c has been shown to give accurate molecular ground-state geometries 28,29 and to provide adiabatic excitation energies in good agreement with experiments for large organic molecules. 30 In the high-temperature, semiclassical limit, quantummechanical modeling of CT using Marcus theory 12,13 proceeds through computing the CT rates according to (3) where V ba is the electronic coupling strength, E r is the reorganization energy, T is temperature, and the activation energy, E A , is calculated as (4) Following a previously described protocol, E r was calculated as the difference between E CT , as obtained in TD-DFT for the ground-state geometry, and the energy obtained after a geometry relaxation using CDFT. 13 As described above, the geometry optimizations of the LE state were performed using the PBEh-3c functional.…”
Section: Methodsmentioning
confidence: 99%
“…Deciphering relaxation phenomena in photoactivated excited states has been a long-standing challenge in chemistry that is particularly relevant for photoactive organic molecules. Next to bulk semiconductors, these compounds are promising for photocatalytic applications, offering many synthetic opportunities for photocatalysis with organic molecules and polymers. A pertinent candidate molecule in this context is rhodamine 6G (Rh6G), a widely available dye that has been found to act as an organic photocatalyst: following earlier work on perylene diimides, the photocatalytic activity of Rh6G has been rationalized by a consecutive photoelectron transfer (conPET) cycle: first, a Rh6G cation present in, e.g., water, is excited by green light and, when reduced by, e.g., ascorbic acid, forms a neutral radical, Rh6G • . When the radical is subsequently excited by blue light, an electron can be transferred to a substrate molecule, which can then undergo a reaction such as a dehalogenation.…”
Section: Introductionmentioning
confidence: 99%
“…AM1.5 illumination conditions) regarding spectral components and corresponding intensities. In addition, it is well-reported in the literature that light of different wavelengths can impact on the selectivity of light-driven chemical reactions [93][94][95][96][97]. For reactions involving homogeneous co-catalysts and more complex mechanisms than water splitting, such as biomass reforming, which include various intermediates and products, the use of a single, selected wavelength to excite charge carriers in the photoelectrode may yield different outcomes compared to conducting the same experiment under broadband light conditions resembling AM1.5.…”
Section: State Of the Art Of Operando Rs Of Semiconducting Photoelect...mentioning
confidence: 99%